The Impact of Teaching on The Skills of Visual Thinking, Psychological Effect and The Development of The Tendency of Pupils in The First Intermediate Students - Sayyid Wahab, Ali Mustafa Al; Al Shammary , Tha'ir Sameer; Al Husainy , Wisal Mu'aayyad (International Journal of Psychosocial Rehabilitation, 2020)
The present research aims at identifying the impact of Buxton and Yager on the acquisition of dictation skills, and to achieve that goal the researcher put the zero hypothesis which states that there is no difference of statistical significance at the level of (0.05) among the average of the marks of the students of the first experimental group that shall study according to the Buxton model, the average of the second experimental group that shall study according to Yager model and the average of the standard group that shall study according to the common method. The researcher randomly chose Al Shuhada’a secondary school for boys at the center of Tal’aafer/ Nineveh governorate, the specimen included 59 students from the first intermediate year divided into 20 students for the first group, 20 for the second and 19 for the standard group. The students of the three groups were chosen similar in the following variants: time age, final marks and the educational level of the parents. The psychometric characteristics of the test were set and after processing the data statistically via mono- variation analysis and at the end of the experiment the researcher performed the dimensional test